HAIR-AN Syndrome: A Rare Cause of Hyper Insulinemic State - Sriram Mudraje; Nancy Garg; Jaideep Khare; Sushil Jindal (Case Reports in Clinical Practice)
Insulin resistance is categorized as type A or type B, depending on the etiology. HAIRAN syndrome is a subtype of type A insulin resistance. It is characterized by high insulin resistance, hyperandrogenemia, and hyperinsulinemia. Here, we present a 12-year-old girl who was lean during her first decade of life and came with complaints of gradual-onset weight gain, darkening of her neck and limbs, and roughening of her skin. Menarche had not been attained. She had Grade 4 acanthosis nigricans, thick coarse skin, and hirsutism. Investigations revealed raised blood glucose, elevated testosterone, elevated fasting insulin, and raised HOMA-IR. With biochemical evidence of hyperandrogenemia, insulin resistance, and the presence of acanthosis nigricans, the diagnosis of HAIR-AN syndrome was made.